2023
DOI: 10.3390/ijms24032288
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish Cancer Avatars: A Translational Platform for Analyzing Tumor Heterogeneity and Predicting Patient Outcomes

Abstract: The increasing number of available anti-cancer drugs presents a challenge for oncologists, who must choose the most effective treatment for the patient. Precision cancer medicine relies on matching a drug with a tumor’s molecular profile to optimize the therapeutic benefit. However, current precision medicine approaches do not fully account for intra-tumoral heterogeneity. Different mutation profiles and cell behaviors within a single heterogeneous tumor can significantly impact therapy response and patient ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 143 publications
(185 reference statements)
0
8
0
Order By: Relevance
“…Many studies have indicated that ZTX models can be used to predict the response of solid tumours to various therapies 35 . For example, a gastric cancer study 19 reported the successful injection of cells from 28 patients (from a total of 46).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have indicated that ZTX models can be used to predict the response of solid tumours to various therapies 35 . For example, a gastric cancer study 19 reported the successful injection of cells from 28 patients (from a total of 46).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, zebrafish is emerging as a timeand cost-effective cancer avatar model to assess tumor phenotype and drug responses. For instance, zebrafish patient-derived xenografts (zPDX) may be suitable for providing precision cancer-medicine pipelines [82].…”
Section: Neuro-phenotypic Complexity In Rasopathies With Insights Fro...mentioning
confidence: 99%
“…zebrafish patient-derived xenografts (zPDX) may be suitable for providing precision cancer-medicine pipelines [82].…”
Section: Neuro-phenotypic Complexity In Rasopathies With Insights Fro...mentioning
confidence: 99%
“…Future cancer studies can further study the role of angiogenesis [ 122 ] and better mimic the human tumor microenvironment [ 129 ], including creating humanized models as achieved in mice [ 142 ]. Finally, so-called cancer ‘avatars’ have application in patient-specific ‘precision’ cancer therapy pipelines, with the potential to directly predict patient outcomes and thus influence individual patient care [ 143 , 144 ].…”
Section: Limitations and Future Prospectsmentioning
confidence: 99%